Analisis Pesan Moral Pantang Menyerah Drama Korea Extraordinary Attorney Woo terhadap Sikap Mahasiswa IAI AL-AZIS - Weny Maulida Nabila; Muhammad N. Abdurrazaq; Elang Bakhrudin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to examine the influence of the moral message of perseverance in the Korean drama Extraordinary Attorney Woo on the attitudes of students at IAI AL-AZIS. Korean dramas often convey strong moral messages that can affect viewers' attitudes. Extraordinary Attorney Woo specifically carries a message about resilience in facing challenges and is widely watched by IAI AL-AZIS students, who feel their attitudes are influenced after watching the drama. This research employs a qualitative method by observing several episodes of Extraordinary Attorney Woo and conducting interviews with seven informants, who are 8th-semester students of IAI AL-AZIS that have watched the drama. Data collection procedures include interviews, observations, and documentation. The findings indicate that the message of perseverance is conveyed through five scenes in episodes 1, 3, and 6, supported by dialogues and character roles that depict perseverance traits, such as enthusiasm, determination, and innovation. Factors that support the value of perseverance in the drama include intention, goals, motivation, and environment. After watching the drama, students reported feeling inspired and motivated to engage in positive behaviors, reflected in their perceptions, emotions, and actions. They were encouraged to adopt a more optimistic outlook and began creating achievement lists as a form of self-motivation.